The Gender Inequality in The Peruvian Labor Market, 2004-2021 - Crispín, Ángel Renato Meneses; Balletta, Mg. Alberto Rojas; Risco, Juan Carlos Ocampo; Untiveros, José Luis León; Pérez, Mg. William Moises Cruzado; Silva, Mg. Omar Cosme (Journal of Ecohumanism, 2024)
The objective of the research is to describe gender inequality in the Peruvian labor market, 2004-2021, identifying the main factors that trigger this problem. The metho-dology applied is documentary type because different articles, works and research reports are collected. For this purpose, a descriptive and comparative analysis was carried out by gender of the following aspects: economically active population, activity rate employ-ment, economically active employed population, labor income, gender wage gap, emplo-yed population in the secondary sector, underemployment, salaried employment and une-mployment. Despite the advances in gender equality, a constant and wide gap remains between men and women in the labor market. Likewise, the results found show that most of the labor market variables by gender have a positive impact and are statistically signifi-cant on the human development index, the estimates would be affected by other gender inequalities that exist in the labor market such as discrimination, stereotypes, among ot-hers.